Β-Lactamase inhibitors: what you really need to know. (October 2017) - Ambrose, Paul G; Lomovskaya, Olga; Griffith, David C; Dudley, Michael N; VanScoy, Brian
Highlights: It's crucial to identify the PK–PD efficacy determinant for a β-lactamase inhibitor. It's crucial to identify β-lactamase inhibitor exposures that prevent resistance. Optimizing β-lactamase inhibitor exposure won't always help prevent resistance. Failure to optimize a β-lactam-β-lactamase inhibitor dose puts the class at risk. Abstract : The world is awash in antibiotic-resistant bacteria. The usefulness of nearly every antibacterial agent available in our hospital pharmacies has been compromised. About half of the recently approved antimicrobial agents for gram-negative pathogens, those pending approval, and those entering clinical development are β-lactam-β-lactamase inhibitor combinations. Thus, we are betting heavily on the efficacy and durability of these agents. However, one needs to be cognizant that poor dose regimen design can result in suboptimal efficacy, on-therapy resistance development, and resistance selection that may harm the activity of all β-lactam-β-lactamase inhibitor combinations. Herein, we discuss three factors that developers and regulators need to consider when evaluating candidate β-lactam-β-lactamase inhibitor regimens: first, know the β-lactamase inhibitor pharmacokinetic–pharmacodynamic efficacy determinant; second, know the β-lactam-β-lactamase inhibitor exposures that prevent antibiotic-resistance amplification; and third, know that an optimized β-lactamase inhibitor dosage regimen won't save you from resistance if the partner β-lactam is suboptimal.